Nierówność głosu a skrzywienie partyjne wyników wyborów: Konsekwencje braku „korekty demograficznej” w wyborach do Sejmu RP - Mazur, Stanisław; Gendźwiłł, Adam (Studia Polityczne, 2024)
The deepening lack of material voting equality (i.e. equal voting power) in elections to the Polish Sejm is one of the key flaws of the electoral system in force in Poland. Inequalities resulting from the improper, i.e. not corresponding to the distribution of population, distribution of seats between constituencies (malapportionment) result from the legislative omission of the Sejm for three consecutive terms. In this article we examine whether maintaining the status quo was associated with systematic party bias, providing electoral benefits to the parties in power and responsible for a possible change in the rules for the distribution of seats. Then, we identify cases of direct benefits and losses from maintaining the status quo for specific MPs seeking re-election (incumbents). Empirical analyses are based on a comparison of the actual election results from 2015, 2019 and 2023 with counterfactual scenarios of introducing the so-called ‘demographic adjustment’. The changes proposed by the National Electoral Commission and resulting directly from the applicable rules of the Electoral Code are more conservative than other variants considered, in particular the nationwide distribution of seats. Although the lack of a ‘demographic adjustment’ generates a partisan bias, the benefits of maintaining the status quo—compared to corrections consistent with the Electoral Code—did not consistently serve the parties in power. The simulated changes in the distribution of seats are not significant from the perspective of the aggregate results of political parties, but greater from the perspective of individual politicians. The results of the analyses suggest that the introduction of a ‘demographic adjustment’ could introduce greater uncertainty in the electoral situation of individual MPs.